Wolf Kahn pastels - Kahn, Wolf, 1927- (Harry N. Abrams, 2000)
"Among the artists who came of age in the 1950s and 1960s, Wolf Kahn chose not to work in the prevailing abstract mode, but instead concentrated on representation, particularly of the landscape. Kahn's work in this vein emphasizes color - at first in austere, tonalist images, and later in brilliant, high-keyed paintings that have established his reputation as one of the most important colorists working in America today."--BOOK JACKET.